PENGARUH PROFITABILITAS, RASIO LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2017 – 2021 - Rachel Alchusna; Zati Rizka Fadhila (Pusat Riset dan Inovasi Nasional, 2022)
Tax avoidance is an attempt to reduce the tax burden but does not violate the applicable tax regulations. This study aims to examine and analyze the effect of profitability, leverage ratio and firm size variables on tax avoidance. In this study, the current assets control variable is used to support the research results. This research includes quantitative research that uses secondary data in the form of financial reports and annual reports. The population in this study were 74 manufacturing companies in the consumption industry sector listed on the Indonesia Stock Exchange in 2017 – 2021. The research sample was selected using the simple random sampling method so that 50 companies were obtained over a 5 year period. Data analysis using multiple linear regression analysis technique. Based on the results of the tests that have been carried out, it shows that the profitability and firm size variables have a positive effect on tax avoidance. while the leverage ratio variable and current assets have a negative effect on tax avoidance. Keywords: Profitability, Leverage and Firm Size, Current Ratio and Tax Avoidance.